2016
DOI: 10.1016/j.joen.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Primary Endodontic Therapy Provided by Endodontic Specialists Compared with Other Providers

Abstract: Introduction: The objective of this study was to compare the outcomes of initial nonsurgical root canal therapy for different tooth types provided by both endodontists and other providers. Methods: By using an insurance company database, 487,476 initial nonsurgical root canal therapy procedures were followed from the time of treatment to the presence of an untoward event indicated by Current Dental Terminology codes for retreatment, apical surgery, or extraction. Population demographics were computed for provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 20 publications
2
51
0
3
Order By: Relevance
“…In this study, complete periapical healing was observed in 87.5 % in MTA-treated, and 75 % in gutta-percha-treated after single-visit endodontic treatment, which is comparable to pervious reports [21]. At 5-years, the survival rate of MTA-treated and gutta-percha treated teeth collectively was 91.6 %, which is equivalent to 92 % survival rate reported in 117818 endodontically treated teeth followed for 5 years retrospectively [23]. …”
Section: Discussionsupporting
confidence: 74%
“…In this study, complete periapical healing was observed in 87.5 % in MTA-treated, and 75 % in gutta-percha-treated after single-visit endodontic treatment, which is comparable to pervious reports [21]. At 5-years, the survival rate of MTA-treated and gutta-percha treated teeth collectively was 91.6 %, which is equivalent to 92 % survival rate reported in 117818 endodontically treated teeth followed for 5 years retrospectively [23]. …”
Section: Discussionsupporting
confidence: 74%
“…Moreover, this type of data analysis, using a one‐point‐in‐time assessment, does not take into account all causal factors that may affect the outcome or progression of periapical healing. Such factors may include the treatment date and specific clinical procedures (Costa et al ), as well as the clinician skills and qualifications (Burry et al ). The convenience sample used in the present study represented a sample of the population that attended 8 different health centres, and consequently, it was not possible to adequately judge the quality of the treatment protocols (Paes da Silva Ramos Fernandes et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The qualification and experience of the clinicians who performed the treatments were unknown and may also be an important factor influencing the outcome (Burry et al . ). Radiographic examination is usually insufficient for a definitive diagnosis and cannot determine the microbiological conditions of the canals.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, information regarding the root canal treatment itself was unavailable, including techniques, instruments, chemicals, materials, isolation, accidents. The qualification and experience of the clinicians who performed the treatments were unknown and may also be an important factor influencing the outcome (Burry et al 2016). Radiographic examination is usually insufficient for a definitive diagnosis and cannot determine the microbiological conditions of the canals.…”
Section: Discussionmentioning
confidence: 99%